Synthesis and functionalization of casein nanoparticles with aptamers for triple-negative breast cancer targeting. (7th November 2022) - Spanu, Chiara; Camorani, Simona; Tortorella, Silvia; Agnello, Lisa; Maturi, Mirko; Comes Franchini, Mauro; Cerchia, Laura; Locatelli, Erica
Abstract : This work shows the synthesis of a drug delivery system made of casein nanoparticles able to host hydrophobic molecules and be functionalized with aptamers targeting the epidermal growth factor receptor. Abstract : This work shows the synthesis of a drug delivery system made of casein nanoparticles able to host hydrophobic molecules and be functionalized with aptamers targeting the epidermal growth factor receptor. In vitro cell viability and uptake analyses, performed on triple-negative breast cancer cells, confirmed the safety profile and the target selectivity.